Description of the final instar larva of Phylloicus paprockii and morphological notes of Phylloicus angustior (Trichoptera: Calamoceratidae) in the Southeastern region of Brazil - Datto-Liberato, Felipe Henrique; Moreira-Silva, Larissa; Paprocki, Henrique (Zootaxa, 2025)
The final instar larva of Phylloicus paprockii is described for the first time, based on material collected in southeastern Brazil. This study also provides new morphological details for the larva of Phylloicus angustior. Both species are diagnosed and compared based on larval traits. The association between immature and adult stages was established through rearing. Diagnostic features of P. paprockii include unique muscle scar patterns, distinct anterolateral pronotal processes, striped legs, and a case built from two large leaf fragments.